Smart Eco-Tourism Mangroves: A Strategy For Revitalizing Coastal Tourism Areas Based On Green Architecture and Information Technology (Community Service Study in the Belawan Mangrove Ecotourism Area, Medan City) - Bhakti Alamsyah; Jusra Tampubolon; Jufri Antoni; Anita Christine Sembiring; Emmiya Ellovani Br Tarigan; Yovita Simangunsong (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Belawan mangrove area in Medan City, Indonesia, possesses significant ecotourism potential yet remains underdeveloped due to inadequate physical infrastructure misaligned with green architecture principles and the minimal utilization of information technology for promotion and visitor management. This community service project aimed to revitalize the area through an integrated